Ball Possession And Passes As Key Performance Indicators In The Algerian League Of Soccer (lfp1) - Hadji, Abderrahmen; Abdelmalik , Bachir Benosmane (Journal of Sport Science Technology and Physical Activities, 2022)
The aim of the present study is to identify if ball possession and pass are key performance indicators in the Algerian league of soccer. 64 games played in the Algerian “Ligue de Football Professionnel 1 (LFP1)“ from the 2015/16 season were analyzed. Attribute of ball possession and pass analyzed are : Ball possession : sequence by ball touch, sequence by time, overall time and possession percentage; Pass: overall number and successful (%), by pitch area, by playing position. Games were analyzed by the Dartfish software. Results showed that neither overall pass and possession (absolute and relative) are related to success. However, we found that defeated teams tend to record more sequence with "7-10" touches (8.5±5.12 vs 7,09 ± 4,23 and 5.1 ± 3.21 for won and draw games ; P<0.05) and more successful passes (%) (P<0.05).Forwards tend to achieve more passes in won games compare to draw and lost ones (P=0.59; 0.06 respectively). Distribution of pass on the field was different in draw games pitch area